ENSINO FUNDAMENTAL DE NOVE ANOS: ANÁLISE E PERSPECTIVA DE AÇÃO - Nájela Tavares Ujiie (Universidade do Oeste Paulista, 2008)
This paper discusses the nine year-old fundamental teaching, in point of view of organizational and methodological questions. This way, it places the education of the childhood in the scenery of the educational politics and it excels for re-doing the course Organizational and of institutionalization of the nine year-old fundamental teaching in the Brazilian educational context. It also presents important points of the methodological and pedagogic demands for the first year of this teaching stage and it focalizes, the Pedagogy of Projects as plausible methodological alternative for the educational work in the initial years of the fundamental teaching, providing a globalizing praxis and it attempts the dynamics of the complexity that involves the education of the childhood.